Modifying Design Criteria for Erosion Control Structures in Arable and Non-arable Land - Adhlkari, R. N.; Rao, M. S. R.; Selvi, V.; Math, S. K. N.; Husenappa , V.; Reddy, K. K. (Indian Forester, 2003)
The 'C' value obtained from standard table by using the rational formula Q = ClA/S60 for arriving at discharges appears to be high under semi-arid conditions of,India, since in many years a high discharge is never observed. 'C' value computed from runoff data recorded under different types of vegetation cover under field conditions are presented in this paper. It is found that the 'C' value is 40 to 60% less than the value presented in the standard table. The value of modified 'C' were tested in a independent watershed in aimilar agroclimatic conditions. By adopting these values it is possible to reduce the section of a structure and thereby the cost. This was tested and it was observed that structures using the modified 'C' values performed satisfactorily. A sample calculation is also shown.